Role-Identity Dynamics in Care and Household Work: Strategies of Polish Workers in Naples, Italy - Kordasiewicz, Anna (Qualitative Sociology Review, 2014)
Migrant household work is a global phenomenon present across geographical contexts. Employing a household worker, especially a worker coming from another country, is a symbolically complex situation that requires interpretive work and negotiations of role-identities from interactional partners. There has been much debate about how to define the relationship between a domestic and/or care worker and her/his employer. It has been argued that the preferred definition by workers themselves is one that centers on work (Anderson 2000). In contrast, “fictive kinship” appears to be the employers’ almost universal strategy, which is usually portrayed in the literature as an exploitative practice (Romero 1992; Anderson 2000; Parreñas 2001; Constable 2003; Lan 2006; McDowell 2006).In this paper, I offer a conceptual grid that consists of hierarchy/equality and distance/intimacy dimensions to examine complex relationships between domestic workers and employers, elaborated during the case study of Polish migrant domestic workers in Naples in 2004. Within the investigated site some elements of the traditional model of service culture have persisted. Migrant workers who come from a post-communist country, and who have rather egalitarian attitudes, have been confronted with these elements. The result has been a clash of definitions over the household worker’s role. Polish women developed two contrasting ways of experiencing and coping with it.The strategies identified in the workers’ narratives are professionalization and personalization, and they refer respectively to emphasizing the professional and the personal dimensions in relations with the employer. They manifest themselves on the levels of action (as narrated by the workers) and narrative construction. The strategies on the level of action aim to shift the situation in a desired direction; the narrative strategies aim at framing the situation in a desired way within a narrative. The text underlines the diversity of migrant response and tentatively assesses the output of different strategies.